Evidence Basis for Regional Anesthesia in Multidisciplinary Fast-Track Surgical Care Pathways. Issue 1 (1st January 2011) - Carli, Francesco; Kehlet, Henrik; Baldini, Gabriele; Steel, Andrew; McRae, Karen; Slinger, Peter; Hemmerling, Thomas; Salinas, Francis; Neal, Joseph M.
Abstract : Fast-track programs have been developed with the aim to reduce perioperative surgical stress and facilitate patient's recovery after surgery. Potentially, regional anesthesia and analgesia techniques may offer physiological advantages to support fast-track methodologies in different type of surgeries. The aim of this article was to identify and discuss potential advantages offerred by regional anesthesia and analgesia techniques to fast-track programs. In the first section, the impact of regional anesthesia on the main elements of fast-track surgery is addressed. In the second section, procedure-specific fast-track programs for colorectal, hernia, esophageal, cardiac, vascular, and orthopedic surgeries are presented. For each, regional anesthesia and analgesia techniques more frequently used are discussed. Furthermore, clinical studies, which included regional techniques as elements of fast-track methodologies, were identified. The impact of epidural and paravertebral blockade, spinal analgesia, peripheral nerve blocks, and new regional anesthesia techniques on main procedure-specific postoperative outcomes is discussed. Finally, in the last section, implementations required to improve the role of regional anesthesia in the context of fast-track programs are suggested, and issues not yet addressed are presented.